The Influence of Company Growth, Company Size, Audit Quality, Previous Year's Audit Opinion, and Leverage on Acceptance of Going Concern Audit Opinions in Banking Companies Registered on the IDX - Saputra, Farhan; Ali, Hapzi; Hermawan, Eric (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This study aims to analyze the factors that affect the going concern audit opinion. The factors used are company growth, firm size, audit quality, audit opinion the previous year, and leverage. The study population were 30 banking companies listed in the Indonesia Stock Exchange since the year 2011-2013. Samples were selected using purposive sampling method. This study uses quantitative methods with logistic regretion analysis model. Results of this study prove that: 1). Company growth, firm size, audit quality, and leverage do not affect the acceptance of going concern audit opinions. 2). Audit opinion the previous year affects the acceptance of going concern audit opinion.